Influence of the environmental heterogeneity on the tree species richness –above ground biomass relationship in the Colombian Amazon (2013)
Abstract: In this study, we aimed to identify the shape and environmental drivers of the species richness (SR) –rarefied above ground biomass (RAGB) relationship across and within tree communities in the Colombian Amazon. We used a series of 130 0.1 ha plots to answer the next questions: 1) what is the shape of the SR - RAGB relationship both across and within tree communities in the Colombian Amazon? 2) At what extent does environmental heterogeneity drives the shape of the SR - RAGB relationship both across and within tree communities? Our results support the idea that in plant studies that cross community boundaries, the hump-shape will be the dominant form of the SR–RAGB relationship. Within communities, on the contrary, the monotonic shape of the SR–RAGB relationship dominated over the expected no shape or the hump-shaped model.Across communities, total bases and P contents were significantly correlated with the SR–RAGB variation. /Across tree communities in the Colombian Amazon, P contents (RMANTEL=0.45) seem to determine a big portion of the coupled variation in SR and RAGB./ Within communities, in contrast, no soil variable played any significant role on structuring the SR–RAGB relationship, and the environmental stress along with the rate of disturbance associated to flooding and bad drainage of soils must play an important role on defining the shape of the SR–RAGB relationship. Overall, the hump-shape of the SR–RAGB relationship found across spatially distributed communities in the Colombian Amazon, showed to come from adding up the within landscape models. Hence, across communities, there is not any single mechanism structuring this pattern, and the combined action of the rate of disturbance along with soil fertility seem to largely determine the up and down slope of the first and third phases of the curve. However, in the second phase of the curve, species neutrality, which means a lack of influence from species competition, seems to be the main mechanism that controls the plateau of the curve where SR becomes the highest